2019
DOI: 10.1038/s41598-019-47968-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo muscle morphology comparison in post-stroke survivors using ultrasonography and diffusion tensor imaging

Abstract: Skeletal muscle architecture significantly influences the performance capacity of a muscle. A DTI-based method has been recently considered as a new reference standard to validate measurement of muscle structure in vivo . This study sought to quantify muscle architecture parameters such as fascicle length (FL), pennation angle (PA) and muscle thickness (t m ) in post-stroke patients using diffusion tensor imaging (DTI) and to quantitatively compare the differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…The fascicles, whose extrapolation length was longer than 30% of the original length, were excluded from further analyses (Bolsterlee et al, 2019) (Figure 2). The 2D pennation angle was computed by subtracting the angle between the fascicle vector (vector connecting both ends of fascicle) and the average normal vector of all the triangles on the MG surface mesh located within a radius of 5.0 mm around the distal end from 90° (Figure 3a), similar to previous studies (Bolsterlee et al, 2019;Körting et al, 2019). It should be noted that this angle is a simulated pennation angle measured in the ultrasonography.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The fascicles, whose extrapolation length was longer than 30% of the original length, were excluded from further analyses (Bolsterlee et al, 2019) (Figure 2). The 2D pennation angle was computed by subtracting the angle between the fascicle vector (vector connecting both ends of fascicle) and the average normal vector of all the triangles on the MG surface mesh located within a radius of 5.0 mm around the distal end from 90° (Figure 3a), similar to previous studies (Bolsterlee et al, 2019;Körting et al, 2019). It should be noted that this angle is a simulated pennation angle measured in the ultrasonography.…”
Section: Discussionmentioning
confidence: 88%
“…The mean values of fascicle length and 2D pennation angle of the selected DTI fascicles were used for comparison with the 3DUS measurements. This approach was conceptually similar to that used in previous studies (Bolsterlee et al, 2015;Körting et al, 2019) and allowed us to compare the architecture of fascicles located at, or close to, the same region. For the regional architecture analysis of DTI-measured fascicles (right MG), the principal component analysis was performed on all of the vertices of the triangular surface mesh of MG (Bolsterlee et al, 2017;Raiteri et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CSAs of the SOL, GM, and GL were estimated based on the magnetic resonance images collected earlier for the subjects using a 3T MRI scanner (Siemens Trio, Siemens Medical Solution, Erlangen, Germany) while lying in a supine position with the identical joint configuration. The detail settings for T1-weighted images were described in our previous study [ 23 ], and the CSAs were identified at the maximal circumference of the lower limb. where i = SOL, GM, and GL, F T is the tendon force, T ankle is the measured ankle torque, ma T is the moment arm, and AR is the ratio of the muscle cross-section area (CSA, Supplementary S2 ).…”
Section: Determination Of Passive Mechanical Properties Of Tendon mentioning
confidence: 99%
“…Compared with conventional methods, such as ultrasound and cadaveric dissection, DTI tractography is able to noninvasively capture a high number of muscle fascicles in superficial as well as deep skeletal muscles. [1][2][3] Most studies have implemented DTI tractography to characterize leg muscle properties [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] except for a few in the arm. 21,22 These previous studies estimated fascicle properties using deterministic algorithms to compute a binary decision for fiber tracking in contiguous voxels.…”
Section: Introductionmentioning
confidence: 99%